Bronchial challenges in athletes applying to inhale a ß2-agonist at the 2004 Summer Olympics - Anderson, S. D.; Sue-Chu, M.; Perry, C. P.; Gratziou, C.; Kippelen, P.; McKenzie, D. C.; Beck, K. C.; Fitch, K. D. (Journal of Allergy and Clinical Immunology, 2006)
Background The International Olympic Committee Medical Commission required a medical justification for athletes to inhale a ß2-agonist before an event at the Summer Games in Athens in 2004.